Tourism, transport and travel management - 3G E-Learning LLC (New York, NY 3G E-Learning LLC, 2023)
"This book is a cohesive and comprehensive look at this multi-million dollar industry sector from a variety of perspectives relevant to the teaching of tourism. Covering all aspects of management of travel and tourism industry, this book looks at the core disciplines and the application of theory to practice." --
Chapter 1 Travel and tourism: an introduction
Chapter 2Air transport
Chapter 3 Globalization agenda in tourism
Chapter 4 Travel agencies and tour operators
Chapter 5 Destination and marketing management
Chapter 6 Cruise tourism management
Chapter 7 Travel intermediation
Chapter 8 Crisis management in tourism
Index.
Editorial board: Aleksandar Mratinkovic, Dan Piestun, Hazem Shawky Fouda, Felecia Killings, Dr. Sandra El Hajj, Fozia Parveen, Igor Krunic, Dr. Jovan Pehcevski, Dr. Tanjina Nur, Stephen and Michelle.
Includes bibliographical references and index.
Keywords: Tourism -- Management; Transportation -- Passenger traffic; Transportation .; Cruise lines -- Management; Travel agents